A Study on the Relationship Between Presence of Women in Boards and Corporate Reputation - Inamdar, Shivani Chetan; Nagendra, Asha (Prabandhan: Indian Journal of Management, 2017)
The presence of women on board has been a debatable issue over the past few years with a limited number of women occupying the senior leadership positions. However, with rapid globalization and changes in the workforce composition, companies need to ensure a substantial presence of women on the corporate board. Existing empirical evidence suggests a positive relationship between the presence of women on board and corporate reputation. Further, with the initiation of campaigns like â€œMake in Indiaâ€ (Government's flagship initiative), which aims to boost the domestic manufacturing industry and other related sectors, a good corporate reputation is much desirable. The present research paper explored how gender composition and industry female employment impacted the presence of women on board and how in turn the presence of women on board impacted the corporate reputation of the firm. In addition, this research study examined whether the presence of women on board mediated the relation between gender composition, industry female employment, and corporate reputation. The regression results indicated a significant impact of independent variable and control variable, that is, gender composition and firm profitability, respectively on corporate reputation. However, no significant result was found for industry female employment and firm size. The presence of women on board had a significant impact on corporate reputation and also mediated the relationship between gender composition and corporate reputation.